Mental Health and Depression in Indonesia: Risk Factors and Service Utilization for Healthy Aging Using SKI 2023 Data - Bhirau Wilaksono; Nurul Mufidah Damry; Nurul Mutiah Aminuddin; Dhini Alfiandari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Mental health conditions, including depression, pose a significant public health challenge in Indonesia, impacting quality of life and healthy aging, particularly among vulnerable populations. This study examines the prevalence of depression and mental health issues, identifies associated risk factors, and evaluates disparities in health service utilization using secondary data from the 2023 Indonesian National Health Survey (SKI 2023). Logistic regression analysis was used to explore associations between mental health outcomes and sociodemographic factors, including age, gender, education, employment, and economic status. The analysis revealed significant geographic and demographic disparities. West Java reported the highest depression prevalence (3.3%) and Bali the lowest (0.3%). Women, unemployed individuals, and those in lower socioeconomic groups exhibited higher prevalence rates. Urban residents had greater access to services compared to rural populations, where stigma and resource limitations were prominent barriers. These findings highlight the urgent need for equitable, community-based mental health initiatives that integrate culturally sensitive care, address social determinants, and reduce stigma. Targeted policies and programs are essential to improving mental well-being, enhancing service accessibility, and supporting healthy aging across Indonesia's diverse populations.